Improving Gender Targeting of Public Expenditures : A Consolidated Note on Lessons and Policy Implications - Ruiz Abril, Maria Elena; Ofosu-Amaah, A. Waafaas (World Bank, Washington, DC, 2013)
This report summarizes policy lessons from the project Improving Gender Targeting of Public Expenditures through Capacity Building. The project, funded by the Bank-Netherlands Partnership Program between July 2007 and December 2009, has supported a combination of analytical work and capacity building activities in the area of Gender-Responsive Budgeting (GRB) in DRC, Liberia, and Rwanda, as well as a regional learning- exchange workshop on gender-responsive budgeting with participants from Kenya, Liberia, Rwanda, and Uganda. The purpose of this policy note is to provide a brief analysis of the key policy issues that emerged from project activities in the three countries.